Pengaruh Model Pembelajaran Project-Based Learning (PjBL) Terhadap Kemampuan Berpikir Kreatif Siswa - Uliya Safitri (Cocos Bio, 2025)
ULIYA SAFITRI (2025). The Effect of the Project-Based Learning (PjBL) Model on Students' Creative Thinking Skills. This study aims to determine the effect of the project-based learning (PjBL) model on the creative thinking skills of eighth-grade students. This research is an experimental study conducted with a quantitative approach. This study used a quasi-experimental design with a nonequivalent control group design, using an experimental group and a control group. The study population was all eighth-grade students (phase D) of SMPN 1 Sukamulia in the 2025/2026 academic year. The research sample was determined using a simple random sampling technique. Phase 8D, the experimental class, used the project-based learning model, and phase 8B, the control class, used the lecture method. Data collection used a modified creative thinking ability test consisting of eight essay questions. Data analysis used an independent sample t-test for hypotheses. The results of the hypothesis show that t count > t table, namely (6.4441 > 2.0017), which means H0 is rejected and H1 is accepted. Therefore, it can be concluded that there is an influence of the Project Based Learning (PjBL) learning model on students' creative thinking abilities. Keywords: Project Based Learning (PjBL), Creative Thinking